Differential modulation using space-time block codes. - Ganesan, G. (IEEE Signal processing letters)
We consider a space-time differential modulation scheme where neither the transmitter nor the receiver has to know the channel. Our scheme is based on the theory of unitary space-time block codes. Compared to the existing differential modulation schemes for multiple antennas our scheme has a much smaller computational complexity. Moreover, our codes have a higher coding gain and lower bit error rate than the codes proposed by other researchers